Cerebral Ischemia 2021
DOI: 10.36255/exonpublications.cerebralischemia.2021.perinatalasphyxia
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic-Ischemic Brain Injury after Perinatal Asphyxia as a Possible Factor in the Pathology of Alzheimer’s Disease

Abstract: Perinatal asphyxia is a common pathological condition occurring worldwide in approximately 4 million newborns annually. The result of this phenomenon is multi-organ damage and the development of chronic hypoxic encephalopathy. It is currently believed that an episode of cerebral hypoxia/ischemia may be one of the major factors responsible for the development of Alzheimer's disease-type dementia and/or Alzheimer's disease. It cannot be ruled out that hypoxia in the perinatal period may be a trigger factor for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 96 publications
0
9
0
1
Order By: Relevance
“…Hypoxia can be not only an isolated pathology but also be associated with a variety of CNS diseases, such as Alzheimer’s disease, Parkinson’s disease, etc. [ 46 , 47 ]. Therefore, approaches that increase the brain’s resistance to hypoxia are of great practical value.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia can be not only an isolated pathology but also be associated with a variety of CNS diseases, such as Alzheimer’s disease, Parkinson’s disease, etc. [ 46 , 47 ]. Therefore, approaches that increase the brain’s resistance to hypoxia are of great practical value.…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal asphyxia in mice causes delayed damage to the hippocampus and associated learning and spatial memory deficits [ 42 , 43 , 44 ]. Significantly higher levels of amyloid protein precursor and total tau protein, increased tau protein phosphorylation, decreased hypoxia-inducible factor alpha [ 45 , 46 ], lower levels of amyloid degrading neprilysin, increased amyloid accumulation with activation of astrocytes and microglia have been shown in the brain after perinatal asphyxia [ 42 , 47 ]. Total tau protein levels in hypothermic-treated ischemic brain injury, as measured by experimental microdialysis [ 47 ], correlated well with neonatal tau protein levels in blood in hypoxic-ischemic encephalopathy treated with hypothermia [ 13 ].…”
Section: Brain Neuropathology After Perinatal Asphyxiamentioning
confidence: 99%
“…There is increasing evidence that the neuropathology induced in the neonate’s brain during and after perinatal asphyxia is similar to that of adult neurodegenerative diseases, such as Alzheimer’s disease [ 13 , 42 , 44 , 45 , 46 , 49 ]. Additionally, one study found elevated plasma levels of tau protein following asphyxia on days 3 and 7 after birth [ 48 ].…”
Section: Brain Neuropathology After Perinatal Asphyxiamentioning
confidence: 99%
“…There is increasing evidence that the pathology induced in the brains of newborns during and after perinatal asphyxia is similar to that found in adult neurodegenerative diseases such as Alzheimer’s disease [ 3 , 13 , 14 , 15 ]. Experimental studies have shown that perinatal asphyxia in mice causes delayed neuronal death in the hippocampus and significant deficits in memory and spatial learning [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have shown that perinatal asphyxia in mice causes delayed neuronal death in the hippocampus and significant deficits in memory and spatial learning [ 13 , 14 ]. In addition, significantly higher levels of tau protein and its increased phosphorylation, higher concentrations of amyloid protein precursor, decreased hypoxia-inducible factor 1 alpha, lower levels of amyloid-degrading neprilysin, an increased accumulation of amyloid with the activation of microglia, and astrocytes in the brain after asphyxia were found [ 3 , 13 , 15 , 16 ]. Furthermore, one study found elevated blood levels of tau protein after asphyxia on postnatal days 3 and 7 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%